2011
DOI: 10.1152/ajpheart.00744.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase 3 deficiency limits adverse ventricular remodeling after pressure overload in insulin resistance

Abstract: Insulin resistance (IR) and systemic hypertension are independently associated with heart failure. We reported previously that nitric oxide synthase 3 (NOS3) has a beneficial effect on left ventricular (LV) remodeling and function after pressure-overload in mice. The aim of our study was to investigate the interaction of IR and NOS3 in pressure-overload-induced LV remodeling and dysfunction. Wild-type (WT) and NOS3-deficient (NOS3(-/-)) mice were fed either a standard diet (SD) or a high-fat diet (HFD) to indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, it is also possible that different or overlapping mechanisms may control the growth of cell bodies and neurites. While some signaling pathways and factors are known to regulate neurite morphology ( Williams and Truman 2005b ; Kurtz et al 2011 ; Yaniv et al 2012 ; Gu et al 2014 ; Medioni et al 2014 ), the factors that shape neuron somata during neuronal remodeling remain undefined. If these mechanisms are different, then this system will provide an opportunity to understand distinct regulatory mechanisms controlling soma and neurite growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that different or overlapping mechanisms may control the growth of cell bodies and neurites. While some signaling pathways and factors are known to regulate neurite morphology ( Williams and Truman 2005b ; Kurtz et al 2011 ; Yaniv et al 2012 ; Gu et al 2014 ; Medioni et al 2014 ), the factors that shape neuron somata during neuronal remodeling remain undefined. If these mechanisms are different, then this system will provide an opportunity to understand distinct regulatory mechanisms controlling soma and neurite growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that eNOS can produce large amounts of reactive oxygen species when deprived of their critical cofactor tetrahydrobiopterin or their substrate L-arginine [49]. In addition, animal models have shown that eNOS confers differential effects on ventricular remodeling and HF, depending on systemic environment such as an insulin resistance state [50].…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic echocardiography was performed as described [25, 26]. LV end-diastolic diameter (LVEDD), fractional shortening (FS), anterior wall thickness (AWT) and posterior wall thickness (PWT) were obtained from M-mode tracings at the level of the papillary muscles.…”
Section: Methodsmentioning
confidence: 99%